ANALISIS KETERKAITAN FUNGSIONAL WILAYAH DAN SEKTORAL PERBATASAN JAWA TENGAH – JAWA TIMUR: IMPLEMENTASINYA DALAM KERJASAMA PPEMBANGUNAN WILAYAH - C. Utomo; Mursid Zuhri (JURNAL LITBANG PROVINSI JAWA TENGAH, 2011)
Incomplete understanding of regional autonomy often results in mis perception of local governments to interpret the implementation of regional autonomy. Sectoral and regional ego often becomes something quite disturbing in the implementation of regional autonomy.Conditions that would inevitably lead to inefficiency pegelolaan local governments aswell asless harmonious relationships among local governments. Sectoral issues, externalities autonomous region, the function of interdependence among regions and the hierarchy of public goods is a fundamental issue underlying the need for regional development and sectoral cooperation. Cooperation among local governments (districts) in one province / provinces into things that must be encouraged. The success and achievements of the cooperation is dependent upon the ability of local governments held a joint daam level of development in their regions. Nevertheless, private and public participation should also be examined and optimized. Along dengankonsep good governance, networking cooperation among the three actors will greatly determine the quality / success of the implementation of regional autonomy. From the study occurred pattern that emerged from the realization of cooperation with local governments to improve the welfare of society is relatively high compared to other regions. The issue of public services and use of natural resources together into a central area of ​​cooperation. Several constraints found in this study on the implementation of cooperation among local governments is still have a diversity of interests and priority areas / sectors of cooperation, still the size dependence to the central government, budgeting issues, and the legality of the law as an umbrella partnership. Therefore, the things to note for sustaining efekktivitas and sustainability of cooperation among districts is to form a strong partnership base. Monitoring the potential, constraints and sectoral cooperation and daerah.Menyusun schemes to be published in order to strengthen the target group and increase the knowledge of stakeholders on the importance of such cooperation.